On the Mother : the chronicle of a manifestation and ministry - Srinivasa Iyengar, K. R. (Sri Aurobindo International Centre of Education, 1978)
On the life and philosophy of La Mère (The Mother), 1878-1973, follower of the Indian philosopher Aurobindo Ghose, 1872-1950.